EVALUASI PROGRAM PELAKSANAAN SISTEM MANAJEMEN MUTU ISO 9001:2008 DI SMK NEGERI 26 JAKARTA - IRSYE ZELVIANA (Jurnal Evaluasi Pendidikan, 2013)
This study aimed to evaluate the implementation program of ISO 9001:2008 Quality Management System (QMS) in SMK Negeri 26 Jakarta. Research using a model-based evaluation of Ralph W. Tyler. Data collected by the instrument of observation, documentation, questionnaires, and interviews. The results showed that the input component to: 1) the planning stage has organizational structures, executive staf, and completeness of the documentation requirements of ISO QMS, 2) the implementation stage ​​the socialization of ISO QMS and procedure how to prepare the documentshave been made, availability of the work program for each area of ​​management, and complete infrastructure facilities, 3) the inspection stage monitoring and audit have been carried out on schedule and under-reporting, and 4) the action stage repair has been carried out in accordance with the specified time limit. At the output component show: 1) improving customer satisfaction aspect of tangibles, reliability, responsiveness, empathy and assurance already well but there is still a teacher who does not comply with a diploma because of a lack of teachers in the study, 2) improving the quality of sustainable resources, educators and education personnel highest qualifications category Masterate (S2) but very less, and 3) improving quality management system in the curriculum both academic and administrative services are well, but educators rarely access the school website as an information media. Management schools in order to socialize and train the educators and education personnel more intensive about ISO QMS.